2020
DOI: 10.1109/tnsm.2020.2972405
|View full text |Cite
|
Sign up to set email alerts
|

BotChase: Graph-Based Bot Detection Using Machine Learning

Abstract: Bot detection using machine learning (ML), with network flow-level features, has been extensively studied in the literature. However, existing flow-based approaches typically incur a high computational overhead and do not completely capture the network communication patterns, which can expose additional aspects of malicious hosts. Recently, bot detection systems which leverage communication graph analysis using ML have gained traction to overcome these limitations. A graph-based approach is rather intuitive, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 48 publications
(74 reference statements)
0
48
0
Order By: Relevance
“…Orabi et al [20] identified 53 different methods in their survey of the bot classification literature. In general, supervised and unsupervised methods can be distinguished [20] that are sometimes even combined [21]. Cresci [22] points out in his survey of the last decade of bot detection research that while the early days of bot detection methods were coined by supervised classifiers focusing on single accounts, more recently, many unsupervised methods [17,23] focusing on groups [23] instead of single accounts were developed.…”
Section: Introductionmentioning
confidence: 99%
“…Orabi et al [20] identified 53 different methods in their survey of the bot classification literature. In general, supervised and unsupervised methods can be distinguished [20] that are sometimes even combined [21]. Cresci [22] points out in his survey of the last decade of bot detection research that while the early days of bot detection methods were coined by supervised classifiers focusing on single accounts, more recently, many unsupervised methods [17,23] focusing on groups [23] instead of single accounts were developed.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many researchers [10]- [18] attempted to analyze the impact of using communication graphs to represent hosts activates. The true structure of network communications, host interactions, and host behaviors are captured by graph-based features derived from high-level flow information.…”
Section: Background and Related Work A Botnet Detectionmentioning
confidence: 99%
“…Botchase [10] applied a hybrid supervised and unsupervised learning with graph-based features to detect botnets. According to the experiments performed by the authors, stand-alone classifiers are insufficient in terms of training time, precision, and overall accuracy performance.…”
Section: Background and Related Work A Botnet Detectionmentioning
confidence: 99%
See 2 more Smart Citations